Methods of solving in‐band ripples and out‐of‐band suppression for yarn tension sensor based on surface acoustic wave. Issue 6 (15th June 2022) - Feng, Yang; Li, Jun; Bai, Ru; Qian, Zhenghong
Abstract: The two key problems of the in‐band ripples and out‐of‐band suppression are proposed in the design of the SAW yarn tension sensor and the methods of decreasing them are achieved. The unbalanced split‐electrode interdigital transducers (IDT) are designed so that the total phase of the regenerated reflection wave and mass load feedback is close to 180°, leading to an effective reduction of the in‐band ripples effect characterised by the sensor frequency response. The engraved bi‐directional slots on the back of the substrate can block the propagation path of the bulk acoustic wave (BAW) to a certain extent, reducing the influence of BAW propagation and suppressing the out‐of‐band suppression of the frequency response. The experimental results show that the SAW yarn tension sensor with the unbalanced split‐electrode IDT can reduce the in‐band ripples from 23.34 to 0.93 dB, and the engraved bi‐directional slots can suppress the out‐of‐band suppression from 28.03 to 7.71 dB.